The Projective Self-Image of the Youth from Labor Migrant Families - Durkalevych, Iryna (Studia Psychologica: Theoria et praxis, 2013)
The article presents the results of empirical research on the self image of youth from different types of families: the full family, temporarily incomplete (labor migration) family and permanently incomplete (divorced) families obtained using the projection method “Draw – a – Family Test”. Comparison of the results obtained by youth from different types of family allows a wider insight into the specificity of today’s functioning of labour migrant family and youth growing up in such kind of families. The study was conducted with the participation of 183 adolescents (92 girls, 91 boys, 14 – 17 years old) from the western areas of Ukraine (Lviv region). The final part of the article contains the main conclusion from empirical research.